Aspects concerning the Judicial Cooperation among the European Member States in Civil and Commercial Matters - Bularca Anca Roxana (Revista Electronica Academico de Direito Brasil-Brazil Panoptica, 2008)
For individuals and companies to be able to exercise their rights wherever they might be in the European Union, the incompatibilities between Member States will have to be removed. For example, at the Tamper European Council in October 1999, European Union leaders presented three priorities for action, mutual recognition of decisions judicial decisions and increased convergence in the field of civil law. Further more, the Council adopted a decision establishing a European judicial network in civil and commercial matters. These instruments aim to improve the judicial co-operation in practice. Since 1968, the European governments have agreed on common rules on jurisdiction and enforcement of judgements in civil and commercial areas. Going further, the Treaty of Amsterdam made judicial co-operation in civil matters a European Community policy linked to the free circulation of people.